1996
DOI: 10.1016/0168-6445(96)00025-3
|View full text |Cite
|
Sign up to set email alerts
|

New trends and opportunities in the development and use of inoculants for silage

Abstract: Inoculants are used as silage additives to improve preservation efficiency and to enhance animal performance. In most commercially available inoculants, homofermentative lactic acid bacteria (LAB) have been used because they are fast and efficient producers of lactic acid, improving natural silage fermentation. Specific LAB inuculants may also have beneficial effects on animal performance even if there is no effect on fermentation. However, these types of inoculants are not always advantageous. They do not nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
158
0
13

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(174 citation statements)
references
References 48 publications
3
158
0
13
Order By: Relevance
“…reduced pH, increased lactate to acetate ratio, or both) by inoculants, whereas DM digestibility (in vitro or in vivo) was increased in only 30% of the trials. Weinberg and Muck (1996), in their review, also reported instances in which fermentation was affected by a LAB inoculant, whereas digestibility was not.…”
Section: Discussionmentioning
confidence: 99%
“…reduced pH, increased lactate to acetate ratio, or both) by inoculants, whereas DM digestibility (in vitro or in vivo) was increased in only 30% of the trials. Weinberg and Muck (1996), in their review, also reported instances in which fermentation was affected by a LAB inoculant, whereas digestibility was not.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, a significant increase in DM content in the inoculated silage was detected during the whole ensiling period (P < 0.001). Similarly, Henderson (1993) and Weinberg and Muck (1996) reported that the treatment of silages with LAB inoculants could improve DM recovery by 1-3%. Furthermore, in barley silage treated with a mixture of bacterial inoculants (Pediococcus, Lactobacillus and Enterococcus spp.)…”
Section: Discussionmentioning
confidence: 99%
“…events during silage fermentation (Weinberg and Muck, 1996). Although the effects of inoculants on the preservation and nutritive value of silage have often been inconsistent, positive outcomes such as higher lactate:acetate ratios, lower ammonia N, decreased DM losses, increased digestibility, improved aerobic stability and enhanced growth performance have been reported (Henderson, 1993;McAllister et al, 1995McAllister et al, , 1998Zahiroddini et al, 2004).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Segundo Muck (1996) (Oliveira et al, 2007;Zanine et al, 2008;Zanine et al, 2009). No entanto, a verificação da silagem inoculada com S. bovis ainda não foi alvo de ensaio de consumo e digestibilidade, com a finalidade de avaliar seu efeito no animal.…”
Section: Introductionunclassified